Management of patients with advanced prostate cancer in the Asia Pacific region: 'real‐world' consideration of results from the Advanced Prostate Cancer Consensus Conference (APCCC) 2017. (19th August 2018) - Chiong, Edmund; Murphy, Declan G.; Akaza, Hideyuki; Buchan, Nicholas C.; Chung, Byung Ha; Kanesvaran, Ravindran; Khochikar, Makarand; Letran, Jason; Lojanapiwat, Bannakij; Ng, Chi‐fai; Ong, Teng; Pu, Yeong‐Shiau; et al.
Abstract : Objective: The Asia Pacific Advanced Prostate Cancer Consensus Conference (APAC APCCC 2018) brought together 20 experts from 15 APAC countries to discuss the real‐world application of consensus statements from the second APCCC held in St Gallen in 2017 (APCCC 2017). Findings: Differences in genetics, environment, lifestyle, diet and culture are all likely to influence the management of advanced prostate cancer in the APAC region when compared with the rest of the world. When considering the strong APCCC 2017 recommendation for the use of upfront docetaxel in metastatic castration‐naïve prostate cancer, the panel noted possible increased toxicity in Asian men receiving docetaxel, which would affect this recommendation in the APAC region. Although androgen receptor‐targeting agents appear to be well tolerated in Asian men with metastatic castration‐resistant prostate cancer, access to these drugs is very limited for financial reasons across the region. The meeting highlighted that cost and access to contemporary treatments and technologies are key factors influencing therapeutic decision‐making in the APAC region. Whilst lower cost/older treatments and technologies may be an option, issues of culture and patient or physician preference mean, these may not always be acceptable. Although generic products can reduce cost in some countries, costs may still be prohibitive for lower‐income patients or communities. The panellists noted the opportunity for a coordinated approach across the APAC region to address issues of access and cost. Developments in technologies and treatments are presenting new opportunities for the diagnosis and treatment of advanced prostate cancer. Differences in genetics and epidemiology affect the side‐effect profiles of some drugs and influence prescribing. Conclusions: As the field continues to evolve, collaboration across the APAC region will be important to facilitate relevant research and collection and appraisal of data relevant to APAC populations. In the meantime, the APAC APCCC 2018 meeting highlighted the critical importance of a multidisciplinary team‐based approach to treatment planning and care, delivery of best‐practice care by clinicians with appropriate expertise, and the importance of patient information and support for informed patient choice.